Trace metal concentration and speciation in storm water runoff on impervious surfaces - Mancinelli, Enrico; Baltrėnaitė, Edita; Baltrėnas, Pranas; Paliulis, Dainius; Passerini, Giorgio; R. Almås, Åsgeir (Journal of Environmental Engineering and Landscape Management, 2015)
Urban storm water runoff (USWR) often transports various trace metals, affecting the quality of receiving waters. Metal concentration and speciation in USWR were investigated by analysing data collected during a storm event on 19 July 2012. USWR samples were taken from a low–traffic intensity road, a pathway in a car–free pedestrian zone, and a galvanized metal roof located in the area of Vingio Park in the city of Vilnius, Lithuania. The metals were mostly in the insoluble form at all three sites, being more than 80% the total amount measured, irrespective of the water quality characteristics and types of surface area. The partitioning coefficient (log Kd) of trace metals decreases in the order Zn > Cu ≈ Mn ≈ Pb >> Cd. The USWR types characterized by a higher pH or dissolved organic carbon(DOC) concentration produced a higher fraction of Cd, Mn, Pb, and Zn bound to fulvic acids (FA).First published online: 24 Nov 2014